Testing of combinations of Density Functional Theory functionals and basis sets for predicting correct geometrical parameters of neutral hexacoordinated Si(bzimpy) 2 complex - Aldongarov, A. A.; Bimukhanov , A. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
we present a study of geometrical parameters of the optimized cluster structure of hexacoordinated Si(bzimpy) 2 complex, containing the 2,6- bis(benzimidazol-2’-yl) pyridine ligand. The purpose of this work is benchmarking different basis sets and functionals to study the Si(bzimpy) 2 . Computational studies were performed using functionals B3LYP, BHandHLYP and CAM-B3LYP and 6-311++g(d,p), cc-pVDZ and cc pVTZ basis sets. Obtained theoretical data of the geometric parameters were compared with the experimental values. On the ground of comparison of theoretical and experimental structural data it was shown that the theoretical method we have used describes Si(bzimpy) 2 silicon complex reasonably well.